AROMA TERAPI MENURUNKAN INTENSITAS DISMENOREA PRIMER PADA REMAJA PUTRI: LITERATURE REVIEW - Nurbaiti, Hanisah (School of Nursing, Faculty of Medicine, Tanjungpura University, 2021)
Background: Primary dysmenorrhea is one of the most common menstrual disorders experienced by young women it has various impacts, including emotional conflicts, tension, anxiety, feelings of discomfort to limiting daily activities. Therefore, an alternative therapy is needed to reduce the intensity of primary dysmenorrhea. Aromatherapy is a complementary therapy that uses essential oils that can be used to treat primary dysmenorrhea. Methods: Literature review, by searching articles journal or previous studies on 7 online databases published between 2016 and 2020. Results: The study selection obtained 19 research articles, then 9 articles were reviewed. Results of the study show that aromatherapy using onion essential oil, olive oil, lime leaves, jasmine, peppermint, oranges, roses, black cumin and ginger given by inhalation, massage, and warm compresses gives a feeling of comfort and relaxation, that can relieves pain, reduce duration and symptoms of primary dysmenorrhea. Conclusion: The use of aromatherapy can reduce the intensity of primary dysmenorrhea in adolescents, so it is recommended for young women to using aromatherapy as a treatment to treat menstrual pain or primary dysmenorrhea during menstruation.